Recurrent Unilateral Nasal Obstruction: A Cause Lying Deep Inside - Biswas, Soumyadeep; Sarkar, Shatanik; Bandyopadhyay, Debasish; Patra, Chaitali (Journal of Nepal Paediatric Society, 2019)
Recurrent nasal obstruction, a common symptom in pediatric practice, can lead to some unusual diagnosis rarely. Non- response to standard treatment warrants further delineation of local anatomy, particularly if symptoms occur unilaterally. Here, we report a case of recurrent unilateral nasal obstruction in a 16 years old girl not amenable to conventional treatment with medicines, which on subsequent investigations revealed an impacted intranasal tooth.